Impact of flow conditions on coliform dynamics in an urban lake in the Brazilian semiarid. Issue 1 (2nd January 2020) - Fraga, Rômulo F.; Rocha, Sofia M. G.; Lima Neto, Iran E.
ABSTRACT: The seasonal and interannual variations of total coliforms (TC) and Escherichia coli (EC) were investigated in an urban tropical lake. Precipitation and flow rate were the controlling parameters influencing coliform dynamics. Correlations were obtained to describe the lake inlet conditions of flow rate, TC and EC. While TC increased with flow rate, EC slightly decreased. This unexpected behaviour for EC was attributed to the counterbalancing impact of coliform loading and surface runoff dilution. Correlations were computed to obtain first-order decay rates of TC and EC as functions of the Reynolds number, assuming the plug-flow model. A general mechanistic-empirical model was proposed to simulate coliform dynamics. The results indicated that seasonal coliform variations are more pronounced than interannual variations. Considering both the plug-flow and complete-mix models, it was shown that eliminating dry weather load reduces TC and EC but still leads to exceedances of the mandatory standards during the rainy season.